Mechanism study on gliding arc (GA) plasma reforming: A combination approach of experiment and modeling. Issue 12 (1st August 2022) - Liu, Jing‐Lin; Gao, Yu; Sun, Bing; Zhu, Bin; Li, Xiao‐Song; Zhu, Ai‐Min
Abstract: Aiming at a deep understanding of the reaction kinetics of gliding arc (GA) plasma reforming, a new approach to combining simulation and experiment is reported. By adding thermodynamic module and conservation equations of mass and energy into the conventional 0D plasma kinetics model, an effective link between experimental diagnostics and reaction kinetics simulation is established for dry reforming of CH4 in GA plasma. The GA plasma parameters are diagnosed experimentally as electron density of 1.4 × 10 14 cm −3, electron temperature of 1.5 eV, and arc gas temperature of 2500 K. The kinetics simulation is implemented based on the obtained plasma parameters and verified by the online analysis of gaseous products. Consequently, the reaction mechanism is revealed by the reliable model. Abstract : This work proposed a new approach to understanding plasma reforming by linking modeling and experimental methods. It allows the 0D kinetics simulation to be available for investigating gliding arc plasma reforming. The required plasma parameters for kinetics simulation are obtained from plasma diagnostics. In addition, the reliability of the kinetics model is verified by the gaseous products' analysis in the experiment. The key reactive species and rate‐determined steps are identified. The detailed reaction pathways are mapped. Then, the relationship between the microscopic reaction kinetics and apparent reactions is disclosed with the reaction pathways.